Spatio-temporal distribution of hospitalizations for chronic Chagas disease and risk factors associated with in-hospital mortality and surgical intervention in Chile. - Nicolhole Atero; Marisa Torres; Angélica Domínguez; Benjamín Diethelm-Varela; Francisca Córdova-Bührle; Fernando O Mardones (Public Library of Science (PLoS), 2024)
Chagas disease (CD) is a neglected parasitic zoonotic disease that affects over 6 million people worldwide. We conducted a retrospective study to analyze the spatiotemporal trends and risk factors for hospitalization rates of CD with cardiac and digestive diagnoses in Chile. We used the Mann-Kendall analysis for temporal trends, Global Moran's Index, and Local Indicators of Spatial Association to identify spatial autocorrelation, and regression models to determine the risk factors associated with in-hospital mortality and surgical intervention. Between 2010 and 2020, a total of 654 hospitalizations were reported, corresponding to 527 individuals. The hospitalization rate steadily decreased over the years (t = -0.636; p = 0.009). The Global Moran's I for the study period showed a positive spatial autocorrelation for hospitalization municipality and for residence municipality of CD patients (I = 0.25, p<0.001 and I = 0.45, p<0.001 respectively), indicating a clustering of hospitalizations in northern municipalities. The most frequent diagnosis was a chronic CD with digestive system involvement (55.8%) followed by a chronic CD with heart involvement (44.2%). The highest percentage of hospital discharges was observed among males (56.9%) and in the 60-79 age group (52.7%). In-hospital mortality risk was higher with increasing age (OR = 1.04), and in patients with cardiac involvement (OR = 2.3), whereas factors associated with the risk of undergoing a surgical intervention were sex (OR = 1.6) and diagnosis of CD with digestive involvement (OR = 4.4). The findings of this study indicate that CD is still a significant public health burden in Chile. Efforts should focus on improving access to timely diagnoses and treatment, reducing disease progression and hospitalization burden, and supporting clinicians in preventing complications and deaths.